2007
DOI: 10.1002/ijc.22851
|View full text |Cite
|
Sign up to set email alerts
|

Survival of squamous cell carcinoma of the head and neck in relation to human papillomavirus infection: Review and meta‐analysis

Abstract: Human papillomavirus (HPV) has been associated with head and neck squamous cell carcinomas (HNSCC), especially of the oropharynx, with highest distribution in the tonsils. HPV infection has been associated with improved outcome, although not all the studies show consistent results. The reason for this is not clear. We reviewed all published articles and conducted a meta-analysis on the overall relationship between HPV infection and overall survival (OS) and disease-free survival (DFS) in HNSCC. Patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
513
3
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(570 citation statements)
references
References 58 publications
27
513
3
11
Order By: Relevance
“…Part of the reasons behind this phenomenon is the increased incidence of high risk human papillomavirus (HPV) related OPSCC [1][2][3]. Interestingly, multiple retrospective studies have shown that patients with HPVpositive OPSCC have a better prognosis compared to patients with HPV-negative tumors [4,5]. OPSCC accounts for the majority of patients enrolled in therapeutic trials for SCCHN and a growing subgroup of these patients have HPV-related carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the reasons behind this phenomenon is the increased incidence of high risk human papillomavirus (HPV) related OPSCC [1][2][3]. Interestingly, multiple retrospective studies have shown that patients with HPVpositive OPSCC have a better prognosis compared to patients with HPV-negative tumors [4,5]. OPSCC accounts for the majority of patients enrolled in therapeutic trials for SCCHN and a growing subgroup of these patients have HPV-related carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that for patients with OPSCC, the overall survival is substantially better among patients with HPV-positive cancer compared to HPV-negative disease [5,[7][8][9][10]. In one highly cited clinical trial [7], high risk HPV infection status was demonstrated as an independent prognostic variable.…”
Section: Introductionmentioning
confidence: 99%
“…Human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC) is increasingly recognized as a distinct disease associated with improved survival and response to therapy [1][2][3][4]. HPV DNA detected in these tumors (predominantly HPV type 16, the most common high-risk type also found in cervical cancer) is frequently integrated and transcriptionally active, with the majority expressing viral oncoproteins E6 and E7 [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…First, although many studies describe a significant association between HPV presence and favorable prognosis, some studies did not find such a correlation. [20][21][22] Second, HPV has also been identified in head-and-neck squamous cell carcinomas of smokers, significantly reducing its favorable effect on clinical outcome. 13 Furthermore, despite the fact that regional lymph node metastasis is considered as the most important prognostic factor in head-and-neck squamous cell carcinomas, 23 this parameter seems to be unreliable in tonsillar squamous cell carcinomas.…”
mentioning
confidence: 99%